Guinea : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Guinea. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2021)
While the non-mining sector was severely impacted by the COVID-19 crisis, overall growth in Guinea remains strong, reaching 7 percent in 2020, driven by booming mining production. Inflation exceeded 12 percent as a result of COVID-related supply disruptions and the ongoing monetary and fiscal response. The already weak social indicators have deteriorated further.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet